Rolling Ball - Learning Cell dalam Pembelajaran untuk Meningkatkan Keterampilan Menulis Bahasa Inggris Siswa - Meiningsih, Sri (Jurnal Paedagogy, 2021)
This study aims to describe the implementation of the Rolling Ball - Learning Cell in learning to improve students' English writing skills. This research method used experimental methods. The subjects of this study were students of class VII A SMP Negeri 27 Surakarta. The research instrument used observation and tests. The data analysis technique of this research used statistical analysis. The results of this study indicate that the implementation of Rolling Ball-Learning Cell in learning English in class VII A SMP Negeri 27 Surakarta includes: the planning stage, preparing the media, and the implementation stage. Rolling Ball-Learning Cell can improve students' English writing skills from the initial conditions with an average score of 75.3 with 43.3% completeness to the condition after treatment an average score of 88 with 90% completeness in class VII A students of SMP Negeri 27 Surakarta.